Rhabdomyosarcoma mimicking Wilms' tumor - Bittencourt, Achiléa Lisboa [UNESP]; Mendonça, Núbia [UNESP]; Schmitt, Fernando [UNESP] (Associação Paulista de Medicina - APM, 1994)
A case of a 6 year old child, with a pleomorphic rhabdomyosarcoma involving simultaneously the leg muscles and the kidney is reported. The renal tumor distorted the pyelocalycial system and Wilms' tumor was the clinical diagnosis. The authors discuss on the possible primary site of the tumor.

É apresentado um caso de rabdomiossarcoma pleomórfico em criança de seis anos envolvendo simultaneamente a musculatura da perna direita e o rim homolateral. O tumor renal distorcia o sistema pielocalicial e teve diagnóstico clinico de tumor de Wilms. Os autores discutem acerca do possível sítio primário do tumor.
Keywords: Renal rhabdomyosarcoma; Wilms' tumor; pediatric cancer; renal metastasis